CAUSES AND CONSEQUENCES OF A CATASTROPHIC MUDFLOWS ON 28 JUNE 2014 NEAR ARSHAN VILLAGE IN THE REPUBLIC OF BURYATIA, RUSSIA - V. K. Laperdin; K. G. Levi; A. M. Lekhatinov; A. V. Kadetova; V. A. Pellinen; A. A. Rybchenko (Геодинамика и тектонофизика)
On 28 June 2014, Arshan village and its heath resort facilities suffered from a shock descent of mudflows from Tunka Goltsy in the Republic of Buryatia, Russia. In this region, the last mudflow descent was recorded in 1971. The article provides an overview of the local natural environment of the site where the mudflows descended and the Kyngarga river flooding took place. Preliminary recommendations are given to ensure protection of the local population and regional infrastructure facilities from natural hazardous phenomena that are typical of sides of riftogenic basins located in the Baikal region.